Focus on what matters, avoid distractions, get things done (Boston, Massachusetts, 2014)
Does it seem like you never have enough time to get everything done? Keeping on top of your tasks, deadlines, and work schedule can be daunting. "Managing Time" quickly walks you through the basics. You'll learn to: - Assess how you spend your time "now"- Prioritize your tasks- Plan the right time to work on each one- Avoid procrastination and interruptions About HBR's 20-Minute Manager Series: Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly read and apply, for ambitious professionals and aspiring executives--from the most trusted source in business.
Keywords: Quản lý thời gian,Time management